The promotion of goodness (al amr bil ma’ruf) (بالمعروف األمر ) and prevention of evil (wa nahyu ‘anil munkar) (المنكر عن والنهي) for sustainable growth of Islamic finance industry - Mhd. Sarif, Suhaimi; Ismail, Yusof (International Journal of Business, Economics and Law (IJBEL), 2016)
Regulatory and bureaucratic rigidity contribute to slowness in the growth of Islamic Finance industry. While conventional finance industry experiencing significant growth, customers of Islamic Finance is becoming skeptical about Islamic finance. This study uses the concept of “promotion of goodness (al amr bil ma’ruf) and prevention of evil (wa nahyu ‘anil munkar)” as enabler for sustainable growth in Islamic Finance industry. The sceptism about Islamic Finance will be replaced with awareness (ta’aruf), mutual understanding (tafahum), mutual assistance (ta’awun) and mutual protection (takaful). In the modern managerial paradigm, managers are expected to get things done in organizations through their fellow colleagues efficiently and effectively. The study uses Ibn Taymiyyah model in operationalizing the promotion of goodness (al ‘amr bil ma’aruf) and prevention of evil (wa nahyu anil munkar) in Islamic Finance industry. The study used personal interview method with 10 senior managers of Islamic Finance to solicit their views about the operationalization of “the promotion of goodness (al ‘amr bil ma’aruf) and prevention of evil (wa nahyu anil munkar)” for sustainable growth of Islamic Finance industry. The respondents suggest the industry to establish collaboration with various key stakeholders to gain confidence, trust and patronage through the ukhuwwah and ummatic activities. The study also proposed 15 actions to use good corporate governance practices to achieve sustainable growth for the Islamic Finance industry.